Explaining Saving–Investment Correlations - Baxter, Marianne; Crucini, Mario J. (American Economic Review, 1993)
National saving and investment rates are highly positively correlated in virtually all countries. This is puzzling, as it apparently implies a low degree of international capital mobility. This paper shows that the observed positive correlation between national saving and investment rates arises naturally within a quantitatively restricted equilibrium model with perfect mobility of financial and physical capital. The model is consistent with the fact that saving–investment correlations are larger for larger countries but are still substantial for small countries. Further, the model is consistent with the finding that current-account deficits tend to be associated with investment booms.